Book Review of "Underestimated: Our Not So Peaceful Nuclear Future" by Henry D. Sokolski - G. Shreekumar Menon (International Journal of Nuclear Security, 2021)
Underestimated: Our Not So Peaceful Nuclear Future by Henry D. Sokolski is a compact book of just three chapters and running 135 pages, but it is likely to unnerve any reader who knows about the growing stockpiles of separated plutonium and stockpiles of highly-enriched uranium. Discussions revolve around the need for a well-protected second-strike capability, the call for a new generation of nuclear weapons that would be easier to use, and the growing interest in the early use of tactical nuclear weapons to quickly de-escalate a conflict. The book commences with the current popular views on nuclear proliferation and proceeds to analyze the consequences of the proliferation of nuclear weapons. Three currently-held views – arms control, hawkish, and academic neorealist – are analyzed in-depth. The first of these schools – arms control – postulates that nuclear weapons are ineffective at deterring aggression, their use is extremely remote, and proliferation is of no vital consequence. To buttress this argument, they cite examples of the Arab-Israeli War of 1973, the Korean and Vietnam wars, and the terror attacks of 9/11 in 2001 and Mumbai in 2008. Hence, John Mueller concluded that “nuclear weapons do a poor job of deterring small or major wars” (9). The Obama administration went on to make reducing nuclear arms a prerequisite for preventing their future spread (6). However, hawkish supporters of nuclear weapons hold the view that reducing American and Russian nuclear arms has a negligible impact on the nuclear ambitions of other countries; North Korea and Iran are cited as apposite examples. Therefore, they believe that nuclear weapons in the U.S. and allied hands help maintain peace.